Hubungan Kualitas Tidur Terhadap Siklus Menstruasi : Studi Pada Remaja di Kabupaten Malang - Saputra, Surya Adi; Hasanah, Zumroh; Puriastuti, Alifia Candra; Amelia, Dessy; Putri, Dinda Farida; Zariroh, Zirroh Alin; Dani, Nova Wulan Rahma (ARTERI : Jurnal Ilmu Kesehatan, 2025)
Menstrual cycle irregularities in the first 2-3 years after adolescents experience menarche are a common problem that is easily found. Adolescents who experience menstrual cycle irregularities are also considered to have disturbances in their sleep quality. This study aims to investigate the relationship between sleep quality and menstrual cycles in adolescents participating in volleyball extracurricular activities at SMPN 1 and SMPN 2 Lawang, Malang Regency. The research design employed an analytical approach, utilizing a purposive sampling technique. The respondents of the study were 55 adolescents. The research instruments used were the Pittsburgh Sleep Quality Index (PSQI) and the Menstrual Cycle Assessment Instrument developed by the author. Data analysis using bivariate, carried out with statistical calculations and displayed in a frequency distribution table. The results of the study were that 45.5% of respondents had abnormal menstrual cycles, and 63.6% of respondents had poor sleep quality. The relationship between the two showed high significance (p-value=0,001), girls who had poor sleep quality had a 9.6 times greater risk of experiencing poor menstrual cycles compared to adolescent girls who had good sleep quality.